The Unique Blue Curcumin - Rahmawati, Dewi (SEAMEO BIOTROP, 2025)
Curcumin, the active compound in turmeric, has long been known for its health benefits. However, did you know that there is a unique variant called Blue Curcumin? Due to its extraordinary potential, this compound has begun to attract the attention of researchers and the health industry. Blue curcumin has extensive health benefits, ranging from antioxidants to anti-inflammatory, antibacterial, and anticancer. In the pharmaceutical industry, blue turmeric can be developed into herbal medicines, cosmetics, essential oils, and health supplements. Identification of blue curcumin species is challenging due to its similarity to other species, color variations, and limitations of conventional identification methods. With a more scientific approach, such as DNA analysis, errors in identification can be reduced. We just started a study to validate the blue curcumin species using a DNA barcoding approach based on the ITS2, rpoC1, and trnH-psbA genes. A wide impact of our study ranges from strengthening species identification, utilization in pharmaceuticals, and increasing economic competitiveness, to biodiversity conservation. We do hope that this study will provide a comprehensive analysis that can help conserve and sustainably utilize this important resource.